COVID-19 PANDEMIC AND ADDRESSING DIGITAL DIVIDE IN MALAYSIA - Sayed Umar, Sayed Mohammad Reza Yamani (Journal of Information Systems and Digital Technologies, 2021)
The recent Covid-19 pandemic outbreak has caused a significant surge in the access and use of digital technology due to the nationwide lockdowns and social distancing norms. The surged move to digitalisation during Covid-19 pandemic is a double-edge sword. Many significant benefits, such as online activities and education, have been provided by the digital transition. However, it has likewise uncoated old bruises of digital divide that are too familiar in information, management and economics research. Covid-19 pandemic has abruptly forced students and youths to engage in online schooling, studies, other virtual social interactions. In this study we address the issues of Information and Communication Technology (ICT) access and use among urban and rural youths in Malaysia, knowledge-based economy (K-economy) and the possible implications for research and practice. We argue that despite the recent Malaysia’s digital progress, the digital divide still persists in many aspects of economy. Yet, some fragments of societies are not able to transcend their limitations of lacking technological devices and skills due to socioeconomic motives. As a result of these limitations, it susceptibly affects youth education attainments, type of jobs and income generations. Therefore, introducing appropriate ICT skills and digital literacies during their lower education will give the better opportunity to them. In summary, it ascribes the inequality factors of digital divide to their motivational and usage accesses. Malaysia need to ensure the economic and potential benefits of the emergence of digital economy. The digital economy helps forwards Malaysia to achieving sustainable and productivity growth, and greater inclusivity.